Eco-friendly graphitic carbon nitride–poly(1H pyrrole) nanocomposite: A photocathode for green hydrogen production, paving the way for commercial applications - Alnuwaiser Maha Abdallah; Elsayed Asmaa M.; Mohamed S. H.; Rabia Mohamed (Open Physics)
The graphitic carbon nitride–poly(1H pyrrole) (g-C3N4-P1HP) composite, formed by seeding onto P1HP, is created through a two-step polymerization process of 1H-pyrrole. In the second stage, g-C3N4 is incorporated, allowing it to blend within the P1HP matrix. The resulting nanocomposite, composed of nanoscale semi-spherical particles, exhibits remarkable efficiency in capturing photons and facilitating energy transfer between particles, making it an ideal candidate for hydrogen (H₂) gas production. This is particularly effective when using common electrolytes, such as natural seawater from the Red Sea or synthetic seawater produced in the lab. To assess its performance, a three-electrode cell was designed, and the H₂ gas output was measured against current density (J ph). The photocathode achieved a current density of −0.65 mA/cm² in natural seawater and −0.62 mA/cm² in synthetic seawater. The hydrogen generation rates were 16.8 µmol/h in natural seawater and 16.0 µmol/h in synthetic seawater per 10 cm², with the natural electrolyte yielding better results. The photocathode’s high sensitivity, efficiency, and environmentally friendly properties – both in materials and electrolytes – underscore the potential of using Red Sea water as a sustainable resource for hydrogen production. These encouraging findings open the door to industrial-scale applications, positioning seawater as a practical solution for renewable hydrogen generation.